The effectiveness of a smartphone-based online peer group on type II diabetes mellitus patients self-empowerment in a primary healthcare center in Indonesia - Ratna Wirawati Rosyida; Ariani Arista Putri Pertiwi; Heny Suseani Pangastuti (Hospital de Clínicas de Itajubá, 2020)
Objective: Self-empowerment is an important factor that influences a person's ability to perform effective diabetes management. One effort that can be done to improve self-empowerment is by providing a smartphone-based online peer-group. This research determined the effect of smartphone-based online peer groups on type 2 diabetes mellitus (T2DM) patients self-empowerment in four primary healthcare centers in Indonesia. Methods: This quasi-experimental research was conducted in four healthcare centers in Indonesia. The total sample was 71 divided into two groups (control and intervention). The control group received standard education from the healthcare center, whereas the intervention group underwent an online peer-group. Self-empowerment was measured before and after intervention using the Diabetes Empowerment Scale-Short Form (DES-SF) questionnaire (Indonesian version). General Linear Model was used in statistical analysis. Results: The mean age of respondents was 56.4 ± 8.8 and 56.9 ± 7.1 years old, 59.5%, and 76.5% had good family support, and 70.3% and 50% of respondents had not received diabetes education for the control and intervention groups, respectively. The average pretest self-empowerment score was 27.03 ± 3.73 and 27.59 ± 3.53 (diff. 0.56; 95%CI -1.16; 2.29), and the post-test score was 27.43 ± 4.13 and 32.76 ± 4.38 (diff. 5.33; 95%CI 3.32; 7.35) for the control and intervention groups, respectively. Online peer-group improve self-empowerment significantly in the intervention group. Conclusion: Smartphone-based online peer-group can improve self-empowerment in patients with T2DM.